Phytochemical, Agronomical and Morphological Responses of Pot Marigold (Calendula officinalis L.) to Foliar Application of Bio-stimulators (Bioactive Amino Acid Compounds) - H Rafiee; A Mehrafarin; A Qaderi; S Kalate Jari; H Naghdi Badi (Institue of Medicinal Plants, ACECR, 2013)
Background: Bio-stimulators as biological substances stimulate metabolism and metabolic processes, which can be increase plants yield and secondary metabolites content. Objective: The aim is to introduce bio-stimulators as bioactive amino acid compounds to increase yield and help to sustainable agriculture. Methods: This experiment was conducted at ACECR on the base of randomized complete blocks design with three replications in 2011. The treatments were commercial formulations of Aminolforte, Kadostim, Fosnutren, Humiforte (each of them 0.75 and 1.5 L.ha-1), chemical fertilizer NPK (70 kg.ha-1), and control treatment (no foliar application). Results: The treatments had significant effect on the studied parameters except SPAD value. Humiforte 1.5 L.ha-1 caused increase in plant dry weight to 37.46%, capitula dry weight to 36.92%, leaf area to 34.44%, relative water content to 32.03%, harvest index to 20.40%, capitula number/plant to 40.64%, total carbohydrates of capitula to 18.43%, total flavonoids of leaves to 19.35%, and total flavonoids yield of leaves to 38.63% compared to control. The highest amount of total flavonoids in capitula (0.25%, with increase to 32% compared to control) was related to Aminolforte 1.5 L.ha-1. Kadostim 1.5 L.ha-1 increased plant height to 36.83%, leaves number to 26.65% and total flavonoids yield of capitula to 38.82%, total carbohydrates of leaves to 13.52%. Content of N, P and K increased with foliar application of bioactive amino acid compounds. Conclusion: Humiforte and Kadostim 1.5 L.ha-1 were the best treatments in regard to existence of amino acid compounds and macro-nutrients of N, P and K in their formulations.